Life Expectancy and Mother-Baby Interventions: Evidence from a Historical Trial - Sonia Bhalotra; Martin Karlsson; Therese Nilsson (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2014)
This paper investigates the potential of maternal and infant health programs to improve the life expectancy of women and children. We study a program trialed in 1931-1933 in seven Swedish medical districts before it was rolled out at the national level in 1937, digitizing and assembling individual data from parish records and birth and death registers and aggregate data from annual reports of medical districts. We estimate short run program effects on (first generation) maternal and infant mortality. In addition, we track individuals exposed to the program together with unexposed individuals from neighboring birth-cohorts so to establish whether they survive to age 40, an age by which maternal mortality of second-generation offspring is determined, and age 75, an age by which 35% of the sample cohorts had died. We find substantial and statistically significant impacts of exposure to the infant program on infant survival and on the probability of surviving to ages 5, 40 and 75, and these impacts are not differentiated by gender. The estimates suggest that the impact on life expectancy is largely driven by infant survival. The program narrowed health inequalities. In particular its impact was systematically larger among children of younger mothers and women who gave birth out of wedlock, who also exhibit higher baseline rates of infant mortality. There is no evidence of endogenous fertility responses or of selection into the program on a range of relevant observables. The evidence is consistent with parents reinforcing treatment by the public health intervention. We are unable to identify any impacts of program components delivered to mothers before birth on either maternal or infant mortality.
Keywords: I15; I18; H41; 330; Maternal care; Infant care; Early life interventions; Barker Hypothesis; Program evaluation; Sweden